Factors influencing sustainability and scale-up of rural primary healthcare memory clinics: perspectives of clinic team members - Debra Morgan; Julie Kosteniuk; Megan E. O'Connell; Dallas Seitz; Valerie Elliot; Melanie Bayly; Amanda Froehlich Chow; Chelsie Cameron (BMC, 2022)
Abstract Background The aging of rural populations contributes to growing numbers of people with dementia in rural areas. Despite the key role of primary healthcare in rural settings there is limited research on effective models for dementia care, or evidence on sustaining and scaling them. The purpose of this study was to identify factors influencing sustainability and scale-up of rural primary care based memory clinics from the perspective of healthcare providers involved in their design and delivery. Methods Participants were members of four interdisciplinary rural memory clinic teams in the Canadian province of Saskatchewan. A qualitative cross-sectional and retrospective study design was conducted. Data were collected via 6 focus groups (n = 40) and 16 workgroup meetings held with teams over 1 year post-implementation (n = 100). An inductive thematic analysis was used to identify themes. Results Eleven themes were identified (five that influenced both sustainability and scale-up, three related to sustainability, and three related to scale-up), encompassing team, organizational, and intervention-based factors. Factors that influenced both sustainability and scale-up were positive outcomes for patients and families, access to well-developed clinic processes and tools, a confident clinic leader-champion, facilitation by local facilitators and the researchers, and organizational and leadership support. Study findings revealed the importance of particular factors in the rural context, including facilitation to support team activities, a proven ready-to-use model, continuity of team members, and mentoring. Conclusions Interdisciplinary models of dementia care are feasible in rural settings if the right conditions and supports are maintained. Team-based factors were key to sustaining and scaling the innovation.